Selanylimidazopyridine Prevents Lipopolysaccharide-Induced Depressive-Like Behavior in Mice by Targeting Neurotrophins and Inflammatory/Oxidative Mediators - Domingues, Micaela; Casaril, Angela M.; Birmann, Paloma T.; Lourenço, Darling de A.; Vieira, Beatriz; Begnini, Karine; Lenardão, Eder J.; Collares, Tiago; Seixas, Fabiana K.; Savegnago, Lucielli (Frontiers in Neuroscience, 2018)
Inasmuch, as the major depressive disorder (MDD), has been characterized as a heterogeneous disease as the inflammatory processes, neurotrophic factors dysfunction and oxidative/nitrosative stress are believed to a play vital role in its establishment. Organoselenium compounds stand out due to their antioxidant, anti-inflammatory, neuroprotective and antidepressant effects. In this sense, the present study investigated the effect of 3-((4-methoxyphenyl)selanyl)-2-phenylimidazo[1,2-a)pyridine (MPI; 20 and 50 mg/kg, i.g.) pretreatment (30 min prior lipopolysaccharide (LPS) challenge (0.83 mg/kg)) on acute LPS induced depressive-like behavior, neuroinflammation and oxidative stress. MPI was able to prevent the increased immobility time induced by LPS on the forced swimming test (FST), prevented the increase in proinflammatory cytokines expression in the hippocampus of mice after LPS challenge via NFkB down-regulation, and prevented the increase of the reactive oxygen species generation and lipid peroxidation in the prefrontal cortex and hippocampus of mice. It was observed that at the doses tested, MPI protected against reducing levels of BDNF in the cortex and hippocampus of mice challenged with LPS. These observations suggest that the antidepressant-like effect of MPI depends on its capacity to modulate the inflammatory, antioxidant and neurotrophic systems.